-2k+3k-9+5k=0

Simple and best practice solution for -2k+3k-9+5k=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2k+3k-9+5k=0 equation:


Simplifying
-2k + 3k + -9 + 5k = 0

Reorder the terms:
-9 + -2k + 3k + 5k = 0

Combine like terms: -2k + 3k = 1k
-9 + 1k + 5k = 0

Combine like terms: 1k + 5k = 6k
-9 + 6k = 0

Solving
-9 + 6k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 6k = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 6k = 0 + 9
6k = 0 + 9

Combine like terms: 0 + 9 = 9
6k = 9

Divide each side by '6'.
k = 1.5

Simplifying
k = 1.5

See similar equations:

| 3/4*29/6 | | 6-10x=43x+17 | | 3(u+4)=(5+u)5 | | -4(5y-6)+2(2y+9)=0 | | x/-8=-2-(-9) | | 2(3k+2)-13k+6+2=0 | | 4(89+67)+4.17159= | | 2(2y+6)+y=2 | | 4/5/5/16 | | 4a-3ab-4ab+3b-6a= | | 7/x+x=20 | | (x^3)(x^2)= | | -7-4=8x+3-7x | | 6(x-2)= | | x/2+3x=8 | | x-4=-x+3 | | -4-(2-3p)=0 | | 51-2x=10-7x | | y=2(3x) | | e^4x=11 | | 540-3x=720-8x | | 11x=5x+48 | | 4x+48=-4x | | -3(x+5)-41=1-30 | | b=4b-24 | | 2x-6=-4x+36 | | Lnx=4.1 | | 12x-6x=30 | | x/6=-3+13 | | 11x-8x=3 | | 4w-14w=20 | | 10/7k+11/7-2k+2/7+2/7k-6=0 |

Equations solver categories